Impact of an Early Discharge Hospital-at-Home Program on Length of Stay and Clinical Outcomes in Preterm Infants: A Case-Control Study. - García Ortega, María Ángeles; García-Piñero, José Miguel; Gómez-González, Alberto José; Medina López, Rosana; González García, Marta; Montero-García, Antonio Jesús; Morales-Gil, Isabel María (MDPI, 2025)
Background/Objectives: Prolonged hospitalization of clinically stable preterm infants may lead to nosocomial infections, interfere with breastfeeding, and hinder parent-infant bonding. We evaluated the impact of an early discharge program with hospital-at-home (HaH) on hospital stay and clinical outcomes among preterm infants. Methods: A retrospective case–control study was conducted in a tertiary neonatal unit (Spain). Fifty infants managed with HaH (2016–2020) were compared with ninety-six controls receiving conventional in-hospital care. Baseline characteristics, growth, and clinical events up to 12 months were collected. Analyses included bivariate comparisons and multiple linear regression for length of stay, adjusted for gestational age, birth weight, sex, and parental factors. Results: Baseline characteristics were comparable between groups. Discharge weight was lower in HaH infants (1865 vs. 2130 g; p < 0.001), but no differences were observed at 6 or 12 months. Length of stay was shorter in HaH infants (26.3 vs. 33.8 days; p = 0.081), and the multivariable model showed an independent 5.5-day reduction (β −5.53; 95% CI −10.96 to −0.11; p = 0.046). Exclusive breastfeeding was more frequent (74% vs.59%; p = 0.08) and significantly longer in HaH infants (141.9 vs. 81.1 days; p = 0.024). No increases were found in complications at discharge, emergency visits (28% vs. 32%; p = 0.7), or readmissions (18% vs. 31%; p = 0.2). Conclusions: Among clinically stable preterm infants, early discharge with HaH was associated with a shorter hospital stay and longer exclusive breastfeeding duration, without evidence of increased morbidity or healthcare use; however, causal inference cannot be established due to the observational design. These findings support the implementation of nurse-led HaH programs as a safe, family-centered strategy for neonatal care.
Keywords: Niños prematuros; Enfermería neonatal; Hospitalización a domicilio; Lactancia materna; Preterm infants; Hospital-at-home; Early discharge; Breastfeeding; Kangaroo mother care; Neonatal nursing; Length of stay